Evidences for functional trans-acting eRNA-promoter R-loops at Alu sequences - Bai, Xue; Li, Feifei; Zhang, Zhihua (bioRxiv, 2021)
Abstract Enhancers modulate gene expression by interacting with promoters. Models of enhancer-promoter interactions (EPIs) in the literature involve the activity of many components, including transcription factors and nucleic acid. However, the role that sequence similarity plays in EPIs, remains largely unexplored. Herein, we report that Alu-derived sequences dominate sequence similarity between enhancers and promoters. After rejecting the alternative DNA:DNA and DNA:RNA triplex models, we proposed that enhancer-associated RNAs, or eRNAs, may directly contact their targeted promoters by forming trans-acting R-loops at those Alu sequences. We showed how the characteristic distribution of functional genomic data, such as RNA-DNA proximate ligation reads, binding of transcription factors, and RNA-binding proteins, align with the Alu sequences of EPIs. We also showed that these aligned Alu sequences may be subject to the constraint of coevolution, further implying the functional significance of these R-loop hybrids. Finally, our results showed that eRNA and Alu elements associate in a manner previously unrecognized in the EPIs and the evolution of gene regulation networks in mammals.